Antibiotic-Producing Streptomyces sp. Isolated from the Soil of a Mangrove Ecosystem - Retnowati, Wiwin; Mertaniasih, Ni Made; Purwanta, Marijam; Wiqoyah, Nurul; , Atika; Maharani, Sekar; Mahdani, Wilda (Folia Medica Indonesiana, 2023)
Highlights: 1. The unexplored soil of mangrove ecosystems in Surabaya, Indonesia, has the potential to be home to biodiversity, including Streptomyces sp. that can produce antibiotics. 2. Streptomyces sp. has antibacterial properties against Gram-positive and Gram-negative bacteria, and the duration of incubation plays a critical role in regulating the antibacterial activity. Abstract A mangrove ecosystem in Surabaya, Indonesia, has a high salinity, pH, potassium, phosphorus, and nitrate contents. This ecosystem comprises a mixture of sand, dust, mud, and clay, which has the potential to be a conducive environment for the isolation of Streptomyces. The importance of Streptomyces in biotechnology lies in its ability to produce bioactive secondary metabolites, which represent a valuable reservoir of antibiotics. This research aimed to assess the antibiotic activity exhibited by Streptomyces sp. isolated from the soil of a mangrove ecosystem in Wonorejo, Surabaya, Indonesia. The analysis focused on the potential of Streptomyces sp. to produce antibiotics that work against Gram-positive bacteria (i.e., Staphylococcus aureus ATCC 25923 and Bacillus subtilis) as well as Gram-negative bacteria (i.e., Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, and Salmonella Typhimurium). The antibacterial activity test was conducted using the modified agar diffusion method. Observations were performed to identify any clear zone formation around the Streptomyces sp. agar colonies with a diameter of 0.8 cm and a height of 3 mm. The clear zone diameter was measured every 24 hours during the 10-day incubation period to assess the diversity of antibacterial activity. The antibacterial profile of Streptomyces sp. exhibited varying levels of activity against different bacterial strains in the tests conducted. The inhibition zone diameters demonstrated the highest levels of activity in Bacillus subtilis (15.9 mm) on day 7, Staphylococcus aureus (27.6 mm) on day 2, Pseudomonas aeruginosa (24.3 mm) on day 7, Escherichia coli (29.2 mm) on day 5, and Salmonella Typhimurium (27.5 mm) on day 7. The results indicated that Streptomyces sp. had inhibitory effects against Gram-positive bacteria as well as Gram-negative bacteria. In conclusion, Streptomyces sp. is a source of biodiversity found in the soil of mangrove ecosystems and has the ability to produce antibiotics.